Pengaruh Karakteristik Keluarga Terhadap Keragaman Pangan Remaja Putri di Kota Denpasar, Bali, Indonesia: Hubungan Karakteristik Keluarga terhadap Keragaman Pangan Remaja Putri di Kota Denpasar, Bali, Indonesia - Ni Wayan Arya Utami; Luh Seri Ani (Amerta Nutrition, 2023)
Background: The three main nutritional problems in adolescent girls are chronic energy deficiency, obesity, and anemia. These problems are associated with food quality or dietary diversity, often influenced by family characteristics. Objectives: This study aimed to determine the association of dietary diversity among adolescent girls in Denpasar City with family characteristics, such as parents' occupation, education and income, type and size of family, government social programs, and food security. Methods: This cross-sectional study was conducted involving 516 adolescent girls selected through a multistage sampling. The first stage involved the selection of 12 villages in 4 sub-districts, and the second involved using simple random sampling to select respondents from each village. Data were obtained using the Minimum Dietary Diversity for Women questionnaire, and Multiple logistic regression was applied to identify the determinant of dietary diversity. Results: The result showed a mean score of 6.7 (SD±1.7) with a maximum of 8.4, and the proportion of inadequate dietary diversity was 11.4%. Based on a bivariable test, six variables were found to be significantly associated with dietary diversity among adolescent girls. After including these variables in a multiple logistic regression model, it was observed that family size (AOR=6.986; 95% CI: 2.718 -17.957; p-value=0.000), mother's education (AOR =1.904; 95% CI: 1.029-3.525; p-value=0.04), and household income (AOR=0.422; 95% CI: 0.227-0.784; p-value=0.006) were significantly associated with dietary diversity. Conclusions: In conclusion, family characteristics, such as having a family size of five or more, a lower level of mother’s education, and household monthly income below the district minimum wage, were significantly associated with inadequate dietary diversity. This condition required intervention in the form of promoting food diversification at the family level.